PENDEKATAN KRITIK SENI TERHADAP DESAIN POSTER KARYA NAUFAN NOORDIYANTO - Putra, M. Edo Pratama; Pangestu, Risvi; Yulius, Yosef (UNIVERSITAS INDO GLOBAL MANDIRI)
Poster is a general term for a letter attached / placard. Posters are placards that are placed in public places, in the form of announcements or advertisements (Big Indonesian Dictionary, 1986: 679). Posters can be interpreted as a form of visual communication work for a wide audience in the format of writing and images, which are generally in the form of stickers on the wall with a communication range for the masses. This study analyzes the works of Naufan Noordiyanto's posters which include studies of the form of the work, design elements, messages and values contained in his poster works with an art criticism approach. Naufan Noordiyanto's poster works mostly on social and political themes, regarding identity, tolerance, equality, philosophy and things that are contemporary in nature. These works were created as a reflection of his experiences, thoughts, and current conflicts. Artist Naufan Noordiyanto has created many forms with changing forms. Many of the body parts that were deformed from the human figures he created appeared to be abnormal human forms. Of course, there is a message that designer Naufan Noordiyanto wants to convey through his works. As in his work, Marlina, which presents Naufan's self-disclosure of the consequences of a lack of equality for a person, and being isolated is sometimes preferable to being recognized through a set of norms in a system that can injure and negate. In this research, the writer uses mimesis theory, expressive theory, and objective / pragmatic theory.